Comparison On Composition And Physical Properties Of Dried Locust (Locusta Migratoria Manilensis) Powder From Different Sources - Vinnie, Ang Jia Wen (Universiti Sains Malaysia, 2020)
Current conventional livestock are no longer sufficient for human consumption in the future due to the increase food demand as global population increasing. Entomophagy could be an alternative protein source with high nutrient composition. Locust (Locusta migratoria manilensis) has the potential with high protein content and qualified as ‘Halal’ that meets Muslim market. The aim of the study is to investigate the differences in proximate composition and physical properties between dried locust powder from two different sources. Both locust powders undergone proximate analysis, colour evaluation, bulk density, tapped density, flowability and compressibility index. Significant difference (p<0.05) in nutritional composition of locust powder from different sources whereby protein content for sample 1 and 2 were 81.4 and 39.7% respectively whereas 6.0 and 23.4% respectively for fat content due to different growth stage of locust. Significant difference (p<0.05) in colour analysis whereby sample 2 had lower lightness and yellowness than sample 1 due to high microwave drying temperature applied in sample 2. Sample 1 had significant (p<0.05) lower bulk and tapped density than sample 2 due to porous structure after freeze-drying treated in sample 1. Both samples were determined as poor flow powder based on flowability and compressibility index due to fine particle size and high moisture content. The study revealed different sample sources do impact on the composition, colour, bulk and tapped of locust powder. Limitation of this study was using different source of locust with different growth stage which resulting in unable to determine the effect of drying method on nutritional composition of locust powder.